Inovasi Mesin Roasting Kopi Berkapasitas 2 kg/jam dengan Pemanas Kompor Portable - Alfadilla, Muhammad Fajar; Abdi, Ferly Isnomo; Sakti, Arya Mahendra; Wulandari, Diah; Rachmattan, Ryan (Jurnal Rekayasa Mesin, 2024)
Robusta coffee beans are the most widely harvested type of coffee beans in Indonesia, but there is still little processing of coffee beans in Indonesia. Some MSMEs in various regions still use traditional methods to roast coffee beans. Roasting coffee beans manually makes the maturity of coffee beans uneven. This research aims to make a coffee roasting machine with a capacity of 2 Kg / hour using a portable stove heater. The method used is by collecting data and then calculating planning and designing tools. Then proceed with the process of testing the function of the tool in achieving a capacity of 2 Kg / hour. The function test is carried out by roasting 500 grams of coffee beans and is carried out 4 times at each specified temperature. The conclusion of this research is that the coffee roasting machine has a length of 41.5 cm, a width of 27 cm, and a height of 50 cm. The drum used has a volume of 3281.7 cm3 which is driven by a 14 W 60 rpm KTYZ motor using a 25 mm diameter timing pulley transmission and a 360 mm long timing belt. The coffee roasting machine can roast 2 kg/hour of coffee beans at 185°C, 190°C, and 195°C through 4 batches of roasting.